A arquitetura do barroco tardio em Minas Gerais: permanências e rupturas - Daniella Coli Chagas (2014)
This thesis discourses on the most advanced expressions of Late Baroque in the state of Minas Gerais in the 1800s, in an attempt to establish the ways in which the style was expressed and the disruptions that occurred. In order to attain a better understanding of this study, it was of primary importance to comprehend the origins of Late Baroque in Europe through the most notable works and architects of Central Europe, based on the Italian treatises. Afterwards, we took into consideration this style development in the North of Portugal, by analyzing the architecture designed by Nasoni, André Soares, and Carlos Amarante. Following, we discerned how this style is set in Brazil throughout the works of the Franciscans in the Northeast, as well as two churches in Rio de Janeiro, by means of adopting a new planimetric typology. Lastly, we considered the works attributed to Anthony Calhoun, important figure within the state of Minas Gerais, who caused many innovations in the architecture of the period. After such considerations, we have proposed a revision of the facades model designed by Sylvio de Vasconcellos, which was based on the progression from rectangular to curved models, and it was considered outdated according to studies conducted by historians over the years. Herewith, we divided this analysis into six discourses which justify the changes made, the last being the central theme of the thesis, i.e, Late Baroque architecture in Minas Gerais: Continuances and Ruptures. With the aim of analyzing this last fraction, we selected a dozen churches which are believed to significantly characterize the Late Baroque style in the 19th Century. They are the Mother Church of Nossa Senhora da Conceição de Antônio Dias in Ouro Preto, Mother Church of Santo Antônio in Tiradentes, Mother Church of Nossa Senhora do Pilar in São João Del-Rei, Mother Church of São João Batista in Barão de Cocais, Mother Church of São Brás do Suaçuí, Mother Church of Nossa Senhora de Oliveira, Nossa Senhora das Mercês e Misericórdia Church in Ouro Preto, Mother Church of Senhor Bom Jesus de Campo Belo, Santo Antônio Cathedral in Campanha, Nossa Senhora da Boa Morte Church in Barbacena, and São José Church in Congonhas do Campo. Finally, as means of completing the analysis, we have also arranged a photographical and architectural survey of all the churches which integrate the corpus of this thesis.